Implementasi Penyelenggaraan Reformasi Birokrasi di Era Otonomi Daerah di Indonesia - Christine Diah Wahyuningsih; Rr. Kurniasih Wilujeng (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to analyze the implementation of government bureaucracy reform in Indonesia using secondary data and qualitative descriptive analysis methods. Bureaucratic reform is an essential step to improve the quality of public services and government effectiveness, particularly at the regional level. The implementation of this reform is expected to create an efficient, transparent, accountable bureaucracy, free from corruption, collusion, and nepotism. Based on the collected data, the results of the study show that although various reform programs have been implemented, the main challenge faced is resistance to change within the bureaucracy itself, as well as a lack of deep understanding of the principles of good governance. This study also identifies the importance of a consistent reward and punishment system to support the success of the reform. Furthermore, strengthening training and enhancing the motivation of civil servants are necessary for the effective implementation of bureaucratic reform. Therefore, awareness and collective commitment from all stakeholders are key to achieving the goals of bureaucratic reform.